Unique regulatory properties of mesangial cells are genetically determined in the rat. - Ping-Chin Lai; Ling-Yin Chiu; Prashant Srivastava; Cristina Trento; Francesco Dazzi; Enrico Petretto; H Terence Cook; Jacques Behmoaras (PLoS ONE)
Mesangial cells are glomerular cells of stromal origin. During immune complex mediated crescentic glomerulonephritis (Crgn), infiltrating and proliferating pro-inflammatory macrophages lead to crescent formation. Here we have hypothesised that mesangial cells, given their mesenchymal stromal origin, show similar immunomodulatory properties as mesenchymal stem cells (MSCs), by regulating macrophage function associated with glomerular crescent formation. We show that rat mesangial cells suppress conA-stimulated splenocyte proliferation in vitro, as previously shown for MSCs. We then investigated mesangial cell-macrophage interaction by using mesangial cells isolated from nephrotoxic nephritis (NTN)-susceptible Wistar Kyoto (WKY) and NTN-resistant Lewis (LEW) rats. We first determined the mesangial cell transcriptome in WKY and LEW rats and showed that this is under marked genetic control. Supernatant transfer results show that WKY mesangial cells shift bone marrow derived macrophage (BMDM) phenotype to M1 or M2 according to the genetic background (WKY or LEW) of the BMDMs. Interestingly, these effects were different when compared to those of MSCs suggesting that mesangial cells can have unique immunomodulatory effects in the kidney. These results demonstrate the importance of the genetic background in the immunosuppressive effects of cells of stromal origin and specifically of mesangial cell-macrophage interactions in the pathophysiology of crescentic glomerulonephritis.